Postoperative Chylous Ascites in Gynecological Malignancies: Two Case Reports and a Literature Review - Xin Tan; GuoLin Luo; Guangdong Liao; Hong Liao (Hindawi Limited, 2024)
Aim. To explore the potential factors that influence the presentation and recovery of postoperative chylous ascites (CA) in gynecological malignancies. Methods. We reported two cases of postoperative CA following gynecological surgery and reviewed the clinical features of 140 patients from 16 relevant papers. Patients' clinicopathological characteristics, surgical approach, and management were summarized. The onset and resolution times of postoperative CA in different groups were analyzed separately. Results. The two patients in our report had recovery after conservative treatments. According to the literature review, the median time of onset of postoperative CA was 5 days (range, 0-75 days) after surgery. The median resolution time was 9 days (range, 2-90 days). Among patients, 87.14% of them had lymphadenectomy during gynecological surgeries, while 92.86% of the patients had resolution after conservative treatments. Conclusions. Lymphadenectomy during surgery may be relevant to the postoperative CA. Conservative management could be the initial choice for postoperative CA treatment.